Why hospital waste management is important to the environment: A systematic literature review - Suriati, Deraman; Lee, Khai Loon; Puteri Fadzline, Muhamad Tamyez (Penerbit Universiti Malaysia Pahang, 2021)
Today, the healthcare industry has grown in importance as the number of hospitals has increased in response to the increased number of patients. This signifies that the world will be facing a more critical environment as a result of waste generation by hospitals. However, there are still insufficient studies that systematically review the existing literature on hospital waste management. Thus, this systematic literature review focuses on hospital waste management and its environmental impact. The results from Google Scholar and Science Direct show 80articles starting from 2015 to 2020. Only 12 articles fulfil the criteria for further analysis. Most studies indicated the presence of hospital waste procedures such as waste segregation, a lack of awareness among clinical staff, poor facilities and government enforcement. The study contributes to the body of knowledge and the industry. This study explains the importance and environmental impact of hospital waste management.A recommendation for futureresearch is provided.